Sustainable Profitability Analysis of Natural Gas-Based Methanol Production - Onuoha Fidelis Wopara; Nnadikwe Johnson (Journal Majelis Paspama, 2026)
Methanol production from natural gas is gaining traction as a sustainable alternative to conventional fuels. This paper presents an economic analysis and design of large-scale methanol production, optimizing synthesis gas composition (CO/CO₂ ratio) for enhanced yield. A Maximum Energy Recovery (MER) heat exchanger network reduces operational costs, achieving a break-even point of 2.69 years. Key results include: production capacity meeting 1% of global demand, total operating cost optimized at 4× raw materials cost, and a fixed-tube sheet heat exchanger (22.54 m²) selected for low-temperature heat exchange. Sensitivity analyses demonstrate robustness against natural gas price fluctuations and methanol market trends, underscoring the process's economic viability and environmental sustainability.